1980
DOI: 10.1002/bjs.1800670904
|View full text |Cite
|
Sign up to set email alerts
|

Cholelithiasis following peptic ulcer surgery: A prospective controlled study

Abstract: An association between gastric surgery and gallstones has been suggested but conflicting conclusions are found in the literature. A prospective study of 118 patients with proved duodenal ulcer disease has been undertaken to determine the true incidence of gallbladder disease. Sixty-one patients undergoing surgery and 57 patients treated medically were matched for age, sex and weight. All patients had oral cholecystography at entry into the study and at 18 months and 109 were reviewed radiologically at 3 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Although a few contrary opinions [22,35,36] exist, this study confirms the previous findings [3,[5][6][7]37] that the GB volume increases after vagotomy or gastrec tomy with [3,5] or without [6,7,37] an impaired GB motor function. The increased GB area we observed around 1 month after surgery persisted henceforth, whereas the impaired contractile response to caerulein returned to normality in 6 months or so.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although a few contrary opinions [22,35,36] exist, this study confirms the previous findings [3,[5][6][7]37] that the GB volume increases after vagotomy or gastrec tomy with [3,5] or without [6,7,37] an impaired GB motor function. The increased GB area we observed around 1 month after surgery persisted henceforth, whereas the impaired contractile response to caerulein returned to normality in 6 months or so.…”
Section: Discussionsupporting
confidence: 90%
“…Although no definite explanation for an increased tendency toward GS formation in postgastrectomy pa tients exists, the most prevailing theories involve the adverse effects of vagotomy which cause a GB motor dysfunction [3][4][5][6][7][8][9][10][11] and an alteration in bile composition or secretion [15][16][17][18][19][20][21][22], The literature gives a wide inci dence range of GSs (10-40%) occurring after vagotomy, with a higher incidence for truncal (11.9-21 %) than for selective vagotomy (2.4-6%) [8. 10], As all the methods of gastrectomy for cancer we have employed inadver tently interrupt both vagal trunks (and more peripheral connections) during the radical lymph node dissection, we did not expect a small incidence of GSs after the sur gery [1].…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase in the frequency of gallstones after a variety of gastric operations including vagotomy and gastrectomy has long been documented [1][2][3][4]. The reason for the high incidence of gallstones following the gastric operations is not completely understood.…”
mentioning
confidence: 99%
“…Some studies have demonstrated an increased risk of development of gallstones after ulcer surgery, while others have failed to demonstrate any risk. 5 Another important question that has not been addressed sufficiently, is whether an eventually increased risk of gallstone formation results in an increased risk of gallstone disease. However, there are no available data on this subject in the literature.…”
Section: Clinical Implications Of Gall‐bladder Dysmotilitymentioning
confidence: 99%